Healthcare resource utilization and treatment costs of Finnish chronic inflammatory bowel disease patients treated with infliximab. (3rd June 2019) - Ylisaukko-Oja, Tero; Torvinen, Saku; Ventola, Hanna; Schmidt, Saku; Herrala, Sauli; Kononoff, Jenni; Voutilainen, Markku
Abstract: Objectives: Inflammatory bowel disease (IBD) is associated with a high economic burden to society due to its early onset and chronic character. Here, we set out to characterize healthcare resource utilization and associated costs in Crohn's disease (CD) and ulcerative colitis (UC) patients with infliximab treatment, the most widely used first-line biologic agent in Finland, in a real-world clinical setting. Methods: This was a retrospective, non-interventional single-center study. Infliximab was administered in routine care, and data were collected retrospectively from electronic health records. All adult anti-TNF naïve CD or UC patients whose infliximab treatment was initiated at the Hospital District of Southwest Finland between the years of 2014 and 2016 were included in the study. Each patient was followed-up for 12 months after the initiation of infliximab treatment. Results: A total of 155 patients were included (45 CD, 110 UC). Altogether, 60.0% ( n = 27) of all CD patients and 43.6% ( n = 48) of all UC patients persisted on infliximab therapy 12 months after treatment initiation. The total cost was similar for both CD and UC cohorts (CD, €10, 243; UC, €10, 770), infliximab treatment being the highest individual cost (60.3% of the total cost in CD; 53.4% in UC). The mean number of infliximab infusions during the 12-month follow-up was 7.0 for CD and 6.5 for UC patients. Conclusions: IBD causes a significant burden to the Finnish healthcare system. This study provides a detailed characterization of the cost landscape of IBD and contributes to optimizing treatment strategies and healthcare resource use in the biosimilar era.